2019
DOI: 10.1681/asn.2018090914
|View full text |Cite
|
Sign up to set email alerts
|

The RNA-Protein Interactome of Differentiated Kidney Tubular Epithelial Cells

Abstract: Background RNA-binding proteins (RBPs) are fundamental regulators of cellular biology that affect all steps in the generation and processing of RNA molecules. Recent evidence suggests that regulation of RBPs that modulate both RNA stability and translation may have a profound effect on the proteome. However, regulation of RBPs in clinically relevant experimental conditions has not been studied systematically. Methods We used RNA interactome capture, a method for the global identification of RBPs to characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…Fig. 1A) 23 . In order to confirm this finding and to show it is not limited to our experiment we screened for the presence of AATF in published RIC datasets.…”
Section: Resultsmentioning
confidence: 97%
“…Fig. 1A) 23 . In order to confirm this finding and to show it is not limited to our experiment we screened for the presence of AATF in published RIC datasets.…”
Section: Resultsmentioning
confidence: 97%
“…Proteins with an FDR lower than 0.05 for enrichment in crosslinked samples (student's ttest) are defined as class II RBPs. Proteins not reaching the criteria for either class I or class II in our study that had been identified as RBPs in previous RIC experiments are defined as “other RBPs” (Hentze et al., 2018, Ignarski et al., 2019, Queiroz et al., 2019, Tamburino et al., 2013, Trendel et al., 2019, Urdaneta et al., 2019). All remaining proteins are summarized under the term “no evidence.” We found that 45% of the proteins co-precipitated with RNA in WT and 38% of the proteins in the vhl-1 mutant fall into either class I or class II (Figure 2A, “RBPome” tab http://shiny.cecad.uni-koeln.de:3838/celegans_rbpome and Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…To further characterize the C. elegans RBPome, we performed an in-depth comparison to published datasets from different model organisms summarized in a recent study (Hentze et al., 2018) and complemented it with an RBPome of murine cells cultured under hypoxia (Ignarski et al., 2019). More than half of class I and class II proteins identified in our study had previously been identified by RIC screens (Figure 2C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent surge of disease-focused reviews have highlighted the emerging clinical interest for therapeutically targeting RBPs in the setting of: neurodegenerative diseases (Hofmann et al, 2019 ; Nussbacher et al, 2019 ), pain disorders (de la Pena and Campbell, 2018 ), cancer (Pereira et al, 2017 ), immunity (Turner and Díaz-Muñoz, 2018 ), diabetes (Nutter and Kuyumcu-Martinez, 2018 ), muscle wasting (Van Pelt et al, 2019 ), reproductive pathologies (Khalaj et al, 2017 ), cardiovascular disease (de Bruin et al, 2017 ), renal injury (Ignarski et al, 2019 ) and hepatic illness (Lee et al, 2020 ). Increased awareness of RBPs as targets has accelerated efforts to develop therapies that disrupt and/or modulate their activity.…”
Section: Rna-binding Proteins As Therapeutic Targets To Modulate Tranmentioning
confidence: 99%